Effect of acute hypohydration on glycemic regulation in healthy adults: a randomized crossover trial - Carroll, Harriet A. (J Appl Physiol (1985), 2019)
The aim of this study was to investigate the acute effect of hydration status on glycemic regulation in healthy adults and explore underlying mechanisms. In this randomized crossover trial, 16 healthy adults (8 men, 8 women) underwent an oral glucose tolerance test (OGTT) when hypohydrated and rehydrated after 4 days of pretrial standardization. One day before OGTT, participants were dehydrated for 1 h in a heat tent with subsequent fluid restriction (HYPO) or replacement (RE). The following day, an OGTT was performed with metabolic rate measurements and pre- and post-OGTT muscle biopsies. Peripheral quantitative computer tomography thigh scans were taken before and after intervention to infer changes in cell volume. HYPO (but not RE) induced 1.9% (SD 1.2) body mass loss, 2.9% (SD 2.7) cell volume reduction, and increased urinary hydration markers, serum osmolality, and plasma copeptin concentration (all P ≤ 0.007). Fasted serum glucose [HYPO 5.10 mmol/l (SD 0.42), RE 5.02 mmol/l (SD 0.40); P = 0.327] and insulin [HYPO 27.1 pmol/l (SD 9.7), RE 27.6 pmol/l (SD 9.2); P = 0.809] concentrations were similar between HYPO and RE. Hydration status did not alter the serum glucose (P = 0.627) or insulin (P = 0.200) responses during the OGTT. Muscle water content was lower before OGTT after HYPO compared with RE [761 g/kg wet wt (SD 13) vs. 772 g/kg wet wt (SD 18) RE] but similar after OGTT [HYPO 779 g/kg wet wt (SD 15) vs. RE 780 g/kg wet wt (SD 20); time P = 0.011; trial × time P = 0.055]. Resting energy expenditure was similar between hydration states (stable between −1.21 and 5.94 kJ·kg(−1)·day(−1); trial P = 0.904). Overall, despite acute mild hypohydration increasing plasma copeptin concentrations and decreasing fasted cell volume and muscle water, we found no effect on glycemic regulation. NEW & NOTEWORTHY We demonstrated for the first time that an acute bout of hypohydration does not impact blood sugar control in healthy adults. Physiological responses to mild hypohydration (<2% body mass loss) caused an elevation in copeptin concentrations similar to that seen in those with diabetes as well as reducing cell volume by ~3%; both of these changes had been hypothesized to cause a higher blood sugar response.